Marketing Strategy Analysis of The Mangrove Forest- Nature Tourism Park, Pantai Indah Kapuk, North Jakarta - Sri Indrayanti; Jana Sandra; Ade Suryana; Sekar Widyastuti Pratiwi (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The Mangrove Forest Tourism Park is one of the conservation forests that can be developed into a Nature Tourism Park. Currently, development has been carried out towards tourism by building facilities for visitors such as mangrove tours, camping areas, interesting photo spots, paddle boats, cafés, and more. This is a qualitative study with a case study approach. Data collection was conducted using semi-structured interview techniques with visitors of the Mangrove Forest Tourism Park PIK and park managers. The researcher also conducted participant observation. To maintain data validity in this study, the researcher used source triangulation. The results of this study show that the marketing mix carried out by the Mangrove Forest Nature Tourism Park, Pantai Indah Kapuk, has not been optimal and requires improvements in terms of product quality, price, and promotional strategy.